Relevansi Tujuan dan Materi Dalam Program Pendidikan dan Pelatihan Pengembangan Guru PAI di Era Digital - Siti Nurjannah; Ali Nurhadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Someone's expertise in a field is sometimes obtained when he has got a job that for him has become a career in his life. However, many of them could not develop their skills in line with the changing times. Where the times are getting more advanced and developing, which of course also demands all human work to be more advanced as well, especially the PAI teacher profession which is often said to be a rigid profession of creative and innovative methods in learning in a technological era. that is why even though one has had a solid career, one still needs education and training (DIKLAT) regarding his professional development. Of course, in conducting education and training, there must be goals to be achieved, such as wanting changes in knowledge, attitudes and skills. From this goal, it will also make it easier to determine the material for the implementation of education and training. So in developing the PAI teacher profession in this digital era, education and training must be carried out in order to create creative Islamic education teachers in utilizing existing technology. And the material that will be delivered during the training is of course also related to how to become a creative teacher in the digital era.